Gas1 mutation extends chronological lifespan via Pmk1 and Sty1 MAPKs in Schizosaccharomyces pombe. Issue 2 (1st February 2020) - Imai, Yuki; Shimasaki, Takafumi; Enokimura, Chihiro; Ohtsuka, Hokuto; Tsubouchi, Satoshi; Ihara, Kunio; Aiba, Hirofumi
ABSTRACT: In the longevity research by using yeasts, chronological lifespan is defined as the survival time after entry into stationary phase. Previously, screening for long lived mutants of Schizosaccharomyces pombe was performed to identify the novel factors involved in longevity. From this screening, one long lived mutant called as No.36 was obtained. In this study, we identified the mutation caused in gas1 +, which encodes glucanosyltransferase ( gas1-287 mutation) is responsible for the longevity of No.36 mutant. Through the analysis of this mutant, we found that cell wall perturbing agent micafungin also extends chronological lifespan in fission yeast. This lifespan extension depended on both Pmk1 and Sty1 MAP kinases, and longevity caused by the gas1-287 mutation also depended on these kinases. In summary, we propose that the gas1-287 mutation causes longevity as the similar mechanism as cell wall stress depending on Pmk1 and Sty1 MAPK pathways. Graphical abstract: : The possible scheme of lifespan extension by gas1-287 mutation. gas1-287 mutation extends chronological lifespan via Pmk1 and Sty1 MAPKs.